"We're just here working on a story:" First Amendment auditors, political culture, and the mediated public sphere. Issue 1 (2nd January 2022) - Leavey, Sean T.
ABSTRACT: This article examines "First Amendment auditing, " a practice in which people use public photography to test the street-level application of civil rights by police and other public employees. Often receiving negative reactions for filming in public places, First Amendment "auditors" record and/or livestream their interactions using YouTube and other platforms to educate and inspire viewers, provide evidence for policy changes, and shame departments into encouraging reforms to individual behaviors and institutional culture. Despite the criticism found in the news and law enforcement media, First Amendment auditors combine Copwatch/Copblock tactics and citizen journalism techniques in a potent form of media activism. Furthermore, due to its broad appeal, First Amendment auditing is a useful site for observing and better understanding the historical, ideological, and discursive tensions affecting the political culture of the contemporary US. By investigating First Amendment auditing, we are able to identify social divisions, and how constitutional values are shared across a range of political subjects, the latter of which being what the US may have to turn toward for democratic stability as it moves into the mid-21st century.